Thermoluminescence of rose quartz from Minas Gerais, Brazil - Martins, R. T.E.K.; Ferreira, I. A.; Silva, A. O.; Nunes, M. C.S. [UNESP]; Ulsen, C.; Künzel, R.; Souza, M. M.; Chithambo, M. L.; Yoshimura, E. M.; Trindade, N. M. (Elsevier, 2023)
This article reports the thermoluminescence (TL) properties of rose quartz from Minas Gerais (Brazil), a translucent pink variety of quartz. Firstly, the sample shows a pure α-quartz phase, based on X-ray diffraction results. Also, the mineral shows a wide optical absorption band at about 500 nm, typical of rose quartz. In addition, X-ray fluorescence showed a high percentage of purity (99.1% of the SiO2), and the inductively coupled plasma optical emission spectrometry (ICP OES) recorded the presence of elements such as Al, Ca, Fe and Ti. The TL measurements were carried out using a commercial Risø TL/OSL reader, model DA-20, equipped with a built in 90Sr/90Y beta source, used to irradiate the sample to different radiation doses (0.01 – 1Gy). The glow curve, measured at a heating rate of 1 K/s, consists of a prominent peak at 355 K followed by other low intensity peaks at higher temperatures. Measurements of the main peak are reproducibility with a coefficient of variation (C.V.) of ∼1.3% and a repeatability of ∼1.8%. Kinetic analysis of the main peak was carried out using experimental methods comprising Tm-Tstop technique, the initial rise method, peak shape estimation and various computational methods (TGCD, TLanal, TLDecoxcel and GlowFit). The peak obeys first order kinetics, with activation energy of 0.86 eV, and a frequency factor of the order of 1011 s−1. Finally, in the dose range studied, the peak shows a sublinear dose response after which supralinearity sets in.
Keywords: Chemical characterization; Dosimetry; Kinetic parameters; Rose quartz; Thermoluminescence